Do elite coaches understand sport scientists? - A study about the usefulness of research data - Esteves, D.; Pinheiro, P.; Bras, R.; O'Hara, K. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Despite the abundance of scientific literature, databases and electronic papers concerning sport sciences (Lippi et al., 2008), there is a general perception that coaches lack operative data to the decision making process (Midgley et al., 2007), that is the major task of the sport training process (Abraham et al. 2006). In this sense, we came to a paradox: the amount of available data may not correspond to the enhancement of sport performance during training process. This paradox may be related to a data overflow problem (Liautaud & Hammond, 2000). Under the scope of contributing to minimise that ``gap`` between research and coaching practice, this work aims (1) to evaluate the usefulness of research data, concerning the needs of the coaches and (2) to propose some major solutions to minimise this problem. This study used a survey to evaluate the perceptions of 47elite coaches in Portugal regarding both the usefulness of data in scientific literature and data overflow problem. Results show that elite coaches lack operative data, or because they perceived is not available for ecologic training process, or it is available but not in an "adequate", understandable language. Among this investigation, we reach several major conclusions: (1) data overflow may be a problem in sport sciences; (2) to do a proper use of available data, it is necessary the implementation of mechanisms in data`s search, selection and treatment, according to Information Management Theory (Eppler & Mengis, 2004; Savolainen, 2007) and (3) research results in sport sciences must be oriented to the training process, and transmitted more efficiently to the coaches (similar results were pointed out by Williams & Kendall, 2007). ABRAHAM, A., Collins, D., Martindale, R. (2006). The coaching schematic: validation through expert coach consensus. J Sports Sci., 24(6), 549-564. EPPLER, M. Mengis J. (2004). The Concept of Information Overload: A Review of Literature from Organization Science, Accounting, Marketing, MIS, and Related Disciplines. The Information Society, 20(5), 325-344. LIAUTAUD, B., Hammond, M. (2000) e-Business Intelligence: Turning Information into Knowledge into Profit. Ed. McGraw-Hill Professional. LIPPI, G., Guidi, G. C., Nevill, A., Boreham C. (2008). The growing trend of scientific interest in sports science research. J. Sports Sci. 26(1), 1-2. MIDGLEY, A. W., McNaughton, L. R., Jones, A. M. (2007). Training to Enhance the Physiological Determinants of Long-Distance Running Performance: Can Valid Recommendations be Given to Runners and Coaches Based on Current Scientific Knowledge? Sports Med. 37(10), 857-880. SAVOLAINEN R. (2007). Filtering and withdrawing: strategies for coping with information overload in everyday contexts. Journal of Information Science, 33(5), 611. WILLIAMS, S. J., Kendall, L. (2007). Perceptions of elite coaches and sports scientists of the research needs for elite coaching practice. J. Sports Sci., 25(14), 1577 - 1586.